Perancangan Aplikasi Bercocok Tanam Padi dan Cabe Kriting Berbasis Android - Harison Harison; Mandarani Putri; Wahida Daratul (Jurnal Nasional Teknologi dan Sistem Informasi, 2017)
The decline in the number of farmers poses a threat to the fulfillment of food self-sufficiency target in Indonesia, as well as the lack of agricultural extension staff. Utilization of information technology can help the problem of agriculture. Utilization of this farming application can help the beginners and farmers in managing their land because the application is equipped with stepping step video from the beginning of processing land to harvest and also accompanied by pest control on each plant. The method used waterfaal method, java programming language and MySqLite database. The results of this planting application is able to provide expert knowledge transfer to the farmers.